2019
DOI: 10.1002/jcp.29014
|View full text |Cite
|
Sign up to set email alerts
|

New trends in glioma cancer therapy: Targeting Na+/H+ exchangers

Abstract: Glioma is the one of the most prevalent primary brain tumors. There is a variety of oxidative stresses, inflammatory pathways, apoptosis signaling, and Na + /H + exchangers (NHEs) involved in the pathophysiology of glioma. Previous studies have indicated a relationship between NHEs and some molecular pathways in glioma.NHEs, including NHE1, NHE5, and NHE9 affect apoptosis, tumor-associated macrophage inflammatory pathways, matrix metalloproteinases, cancer-cell growth, invasion, and migration of glioma. Also, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 95 publications
0
16
0
Order By: Relevance
“…The strategy of ion channel blockades accompanies maintaining the low intracellular pH in malignant cells, which induce acid-mediated metabolic collapse following by apoptosis or necrosis [282,283]. For instance, targeting of NHE1 recently reported to be effective in the treatment of glioblastomas, as highly glycolytic and strongly pH-dependent malignancies [284,285]. It has also been shown that proton pump inhibitors (PPI, V-ATPase blocker) increase the uptake and effect of cytotoxic drugs in chemo-resistant epithelial ovarian cancer [286].…”
Section: Targeting Hypoxia-induced Metabolic Changes As a Therapeutic Strategymentioning
confidence: 99%
“…The strategy of ion channel blockades accompanies maintaining the low intracellular pH in malignant cells, which induce acid-mediated metabolic collapse following by apoptosis or necrosis [282,283]. For instance, targeting of NHE1 recently reported to be effective in the treatment of glioblastomas, as highly glycolytic and strongly pH-dependent malignancies [284,285]. It has also been shown that proton pump inhibitors (PPI, V-ATPase blocker) increase the uptake and effect of cytotoxic drugs in chemo-resistant epithelial ovarian cancer [286].…”
Section: Targeting Hypoxia-induced Metabolic Changes As a Therapeutic Strategymentioning
confidence: 99%
“…As a result of these findings, both NHE and the cancer-specific pHi/pHe proton reversal can nowadays be considered to be the new and main key actors in the etiopathogenesis of MG. Indeed, the main molecular, biochemical and metabolic factor blamed for the onset of MG is the NHE exchanger isoform 1 (NHE1) and, secondarily, other NHE isoforms like NHE5 and NHE9 [30]. In summary, during the last few years, the new hydrogen ion (H + )-related perspective of a wide array of cancers, and of MG too, has progressed from the original Warburg approach to glycolytic cancer metabolism to a post-Warburg pH-centered paradigm.…”
Section: Towards a New Perspective And Clinical Approach To Malignmentioning
confidence: 99%
“…In the same line, the determination of the effects of different anticancer drugs on pHi is a new and most promising area of research, not only in therapeutics but also in the diagnosis and degree of extension of MG, at least in GBM. This new pH-centered tool allows us to test, even in individual tumors, the sensitivity to IA of different pH-sensitive anticancer drugs such as topiramate, lonidamide, quercetin, dichloroacetate (DCA) and cariporide [30,36,120,121,122,123,124,125,126]. Finally, increasingly sophisticated methodologies to determine pHi and pHe in malignant tumors are being published, while recent and complete reviews on the subject are also available [127].…”
Section: Towards a New Perspective And Clinical Approach To Malignmentioning
confidence: 99%
“…Cancer is still one of the increasing challenges worldwide (Shabaninejad et al, 2019; Tamtaji et al, 2020). The field of cancer therapy has undergone a number of changes.…”
Section: Anti‐tumor Activity Of Curcuminmentioning
confidence: 99%